Upper and Lower Face and Ideomotor Apraxia in Patients with Alzheimer’s Disease - Jay Guido Capone; Sergio Della Sala; Hans Spinnler; Annalena Venneri (Behavioural Neurology)
Introduction: Apraxia of face movement in Alzheimer's disease (AD) has been rarely investigated. This study aimed at investigating the frequency of lower (mouth, tongue and throat) and upper (eyes and eyebrows) face apraxia, in AD and its relationship with limb apraxia and severity of dementia.